Time-of-Day-Dependent Physiological Responses to Meal and Exercise - Aoyama, Shinya; Shibata, Shigenobu (Frontiers in Nutrition, 2020)
The mammalian circadian clock drives the temporal coordination in cellular homeostasis and it leads the day-night fluctuation of physiological functions, such as sleep/wake cycle, hormonal secretion, and body temperature. The mammalian circadian clock system in the body is classified hierarchically into two classes, the central clock in the suprachiasmatic nucleus (SCN) of the hypothalamus and the peripheral clocks in peripheral tissues such as the intestine and liver, as well as other brain areas outside the SCN. The circadian rhythm of various tissue-specific functions is mainly controlled by each peripheral clock and partially by the central clock as well. The digestive, absorptive, and metabolic capacities of nutrients also show the day-night variations in several peripheral tissues such as small intestine and liver. It is therefore indicated that the bioavailability or metabolic capacity of nutrients depends on the time of day. In fact, the postprandial response of blood triacylglycerol to a specific diet and glucose tolerance exhibits clear time-of-day effects. Meal frequency and distribution within a day is highly related to metabolic functions, and optimal time-restricted feeding has the potential to prevent several metabolic dysfunctions. In this review, we summarize the time-of-day-dependent postprandial response of macronutrients to each meal and the involvement of circadian clock system in the time-of-day effect. Furthermore, the chronic beneficial and adverse effects of meal time and eating pattern on metabolism and its related diseases are discussed. Finally, we discuss the timing-dependent effects of exercise on the day-night variation of exercise performance and therapeutic potential of time-controlled-exercise for promoting general health.